Case Report: Metagenomics Next-Generation Sequencing Can Be Performed for the Diagnosis of Disseminated Mucormycosis - Sun, Yi; Li, HuiLing; Chen, JiaJun; Ma, ZhongHui; Han, Pin; Liu, YuChen; Wen, Jing; Ren, Fang; Ma, XiaoXu (Frontiers in Medicine, 2021)
Mucormycosis is an infection caused by a group of filamentous molds with in the order Mucorales. In developing countries, most cases of mucormycosis occur in persons with poorly controlled diabetes mellitus or subjects with normal post-traumatic immune function. Mucormycosis exhibits a marked propensity to invade blood vessels. The mortality rate of invasive mucormycosis is very high (> 30-50%), and 90% of the mortality is related to disseminated diseases. We report a 62-year-old man with underlying diseases such as diabetes and psoriatic arthritis with a history of trauma before admission. Chest CT showed multiple cavities. Based on the suspected clinical manifestation of mucormycosis infection, the patient received microbiological culture of bronchoalveolar lavage fluid and Metagenomics Next Generation Sequencing, and the results suggested Klebsiella pneumoniae infection. However, Rhizopus microsporus strains were shown in transpulmonary puncture tissue Metagenomics Next Generation Sequencing. Therefore, we report a case in which rare pathogens were identified by Metagenomics Next Generation Sequencing.